Psychological Profiling of Triathlon and Road Cycling Athletes - Olmedilla, Aurelio; Torres-Luque, Gema; García-Mas, Alexandre; Rubio, Victor J.; Ducoing, Eugenio; Ortega, Enrique (Frontiers in Psychology, 2018)
Psychological characteristics of athletes play a key role in sport performance and may moderate and mediate the influence of technical, tactical and physical abilities athletes show. Different authors have emphasized the special attention such psychological characteristics should receive considering the extent they can influence athletes’ behavior either in training or in competition. This paper is aimed at describing the psychological profiles of two cycling sports: triathlon and road cycling. One hundred and twenty-nine male and female professional and amateur cycling athletes (35.74 years old average age ±12.79; 14.94 average number of years practicing cycling ±11.20) were assessed on different psychological characteristics. For that purpose, the Psychological Characteristics related to the Sport Performance (CPRD) Questionnaire, Psychological Skills Inventory for Sports (PSIS), was used. Results showed significant differences among triathlon and road cyclists (Stress control = t116=-3.711, p=.000, d=.48 ; Influence of Performance Evaluation = t115=-3-115, p=.002, d=.49; Motivation = t124=-5.520, p=.000, d=.82; Mental Skills = t119=-4.985, p=.000, d=1.02). There were no significant differences between men and women though there were differences among pros and amateur athletes. Triathlon professional, compared to amateurs, showed higher scores in all the psychological dimensions assessed (Stress control= t85=3.005, p=.003, d=1.07; Influence of Performance Evaluation= t83=2.858, p=.005, .77; Motivation= t91=2.721, p=.008, d=.26; Mental Skills= t87=2.556, p=.012, d=.77). The results of this descriptive study contribute to stablish a model of optimal psychological profiling applied to the different cycling groups that can be used by sport psychologist, trainers and coaches in order to promote peak performance of these athletes.